For a $\triangle ABC$ with side lengths $a,b,c$ and circumradius $R$ prove that-

$a+b+c\leq 3\sqrt3 R$

Now we know that $R=\frac{abc}{4\Delta}$ where $\Delta$ denotes area of triangle. So I tried to reduce inequality as follows to find hint of using $AM-GM$

$a+b+c\leq 3\sqrt3 \frac{abc}{4\Delta}$

$(a+b+c)^2\leq 27 \frac{(abc)^2}{16\Delta^2}$

$\displaystyle(a+b+c)^3(a+b-c)(b+c-a)(c+a-b)\leq \frac{27(abc)^2}{16}$

Now I know that which terms I have to incorporate in $AM-GM$ but I'm not able to correctly use them

Please provide me hint so that I can proceed forward

  • $\begingroup$ Several hi(n)ts from approach0.xyz, as expected. $\endgroup$
    – dxiv
    Jun 7 at 6:37

Use the sine rule $$ a = 2R\sin A$$ $$ b = 2R\sin B$$ $$ c = 2R\sin C$$ Now, you have to prove that $$2R\sin A + 2R\sin B + 2R\sin C \le 3\sqrt3R$$ $$ \sin A + \sin B+ \sin C \le \dfrac{3\sqrt3}{2}$$ Can you complete it from here?

Hint: This can be easily proved using Jensen's inequality.

  • $\begingroup$ Yes now I can take it forward since$\ sin x$ is convex up for the interval $(0,\pi)$, Therefore $(\sin A+\sin B+\sin c)/3 \leq \sin( (A+B+C)/3)=\sqrt{3}/2$ $\endgroup$ Jun 7 at 6:39

We know that $R \ge 2r$$R \ge 2r=\frac{2Δ}{s}=2\sqrt{\frac{(s-a)(s-b)(s-c)}{s}}\ge 2(\frac{3s-a-b-c}{3})^\frac32\cdot \frac{1}{\sqrt{s}}=2(\frac{s}{3})^\frac32\cdot \frac{1}{\sqrt{s}}=\frac{2s}{3\sqrt3}=\frac{a+b+c}{3\sqrt3}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.